Maedi-Visna: general aspects and impacts on sheep farming - Andrade, Elisa; Saraiva, Naianne; Rehfeld, Izabelle (Pubvet, 2021)
The purpose of this review is to cover the different aspects of Maedi-Visna, a chronic, multisystemic disease caused by a virus of the genus Lentivirus and family Retroviridae. Small ruminants are affected, with a higher occurrence in sheep. It is widely distributed throughout the world and in Brazil, leading to serious economic problems in sheep farming. Transmission of the virus occurs mainly through the respiratory route, through aerosols, and through the digestive route with the ingestion of colostrum and milk containing the virus. Infected animals become progressively slimmer, although most of them are asymptomatic and pneumonia, arthritis, mastitis and encephalitis may be present. Because it is a chronic disease, it is more difficult to find clinical evidence, so the diagnosis should be confirmed by laboratory tests based on antibody detection or identification of the etiological agent. There are no vaccines or treatments to prevent the disease, therefore management practices should be adopted to prevent it, as discarding positive animals associated with separating offspring from positive females at birth.